Non-communicable Chronic Diseases and the COVID-19 Pandemic - Miguel Ángel Serra Valdés (Universidad de las Ciencias Médicas de Cienfuegos, 2020)
In the last 40 years, humanity has been affected by three major pandemics that have provoked many deaths: the increase in the incidence and prevalence rates of chronic non-communicable diseases, the pandemic of human immunodeficiency virus / AIDS and currently the pandemic by COVID-19. The objective of this article is to publicize the relationship between chronic non-communicable diseases and COVID-19, despite the fact that there are still unknowns about this new disease and the reasons for the high mortality it causes. The repercussion of the pathogenesis of this disease in chronic diseases is analyzed. Mortality is high mainly in patients aged over 60 and with associated chronic non-communicable diseases where it has atypical manifestations and devastating effects. The emergence of this new human infectious disease caused by an unknown pathogen highlights the challenge of emerging infectious diseases and the importance of permanent preparation to deal with them. This environment brings fear, misinformation and many unknowns that remain to be clarified with future research.